The rise of quality assurance in Asian higher education - Shah, Mahsood; Do, Quyen T.N. (Cambridge, MA, United States : Chandos Publishing, 2017)
The rise of quality assurance in Asian higher education provides information on the well researched quality assurance frameworks, processes, standards, and internal and external monitoring that have taken place around the globe. However, in Asia, where higher education has witnessed rapid growth, and is also contributing significantly to international education which is benefited by many developed countries, this data has not been readily available. In recent years, governments in Asia have made significant investment with an aim of creating education hubs to ensure that higher education is internationally competitive. This book examines the developments in higher education quality assurance in eleven Asian countries, providing systematic insights into national quality assurance arrangements and also examining the different approaches governments in Asia have implemented based on social and economic contexts. Includes chapters from eleven countries that examine quality assurance arrangements. Explores untold case studies of countries, such as Mongolia, Uzbekistan, Kazakhstan, Cambodia, Indonesia, Thailand, Korea, India, and others. Examines higher education context, quality assurance arrangements, effectiveness, challenges, and international quality assurance in Asia. Offers contributions from leading scholars and practitioners who are working in higher education in Asia.
1. Stakeholder Views of Quality Assurance in Cambodian Higher Education 2. Quality Assurance in Chinese Higher Education 3. Quality Assurance in Hong Kong: Fit for Cultural Perception 4. Quality Assurance in Higher Education- An Indian Experience 5. The rise of quality assurance in Indonesian higher education 6. Quality Assurance in Higher Education of Kazakhstan 7. A Review of the System and Issues 8. Quality Assurance System in Korean Higher Education: Development and Challenges 9. Quality Assurance and Quality Enhancement in Malaysian Higher Education 10. Quality Assurance Mechanisms in Mongolian Higher Education 11. The Rise of Quality Assurance in Thailand 12. Transforming Higher Education in Uzbekistan: from Quality Control to Quality Assurance Culture 13. Quality assurance in Vietnamese higher education: a top-down approach and compliance-driven QA
Includes bibliographical references and index.
IQAC
Trim Education
Keywords: Education, Higher -- Asia -- Evaluation; Education, Higher -- Evaluation; Asia